Exchange Rate Volatility and Trade Deficit in Pakistan: A Time Series Analysis - Soharwardi, Mariam Abbas; Ahmad, Mumtaz; Shafique, Muhammad Nouman (International Journal of Economics and Financial Issues, 2020)
This paper inspected the exchange rate volatility in Pakistan within the time of 1981m07 to 2013m04 at that point discover its impacts on trade deficit. ARCH and GARCH models are developing for catching the unpredictability impact of exchange rate volatility in Pakistan. Exchange standard unpredictability was figured in numerous past investigations by taking the standard deviation of the moving normal of the logarithm of exchange rate. In any case, in this paper exchange rate unpredictability is estimated by ARMA (0, 1) and ARCH/GARCH (2, 1) models and asymmetrical information is utilized as dummy variable. Exchange rate volatility is utilized as independent variable and trade deficit as dependent variable. Cash supply, private investment and gross domestic product are utilized as control variable. ADF (Augmented Dickey-Fuller) test used to check the stationary of the information the aftereffects of ADF demonstrates that a few factors are stationary at first contrast have request of joining I (1) and a few factors are stationary at level have request of reconciliation I(0). We utilize ARDL (Autoregressive distributed lag model) to break down the impact of exchange rate unpredictability on trade deficit. The outcomes appeared there is negative and huge long run connection between exchange rate unpredictability and trade deficit yet in short run it is noteworthy and positive. Keywords: Volatility, ARCH effect, Trade Deficit, ARDL JEL Classifications: E52, E58, F31 DOI: https://doi.org/10.32479/ijefi.9528